Celebrity Endorsements And Its Brand Love On Purchase Intention At E-Marketplace - Catharina Clara (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2023)
Advertised brands are frequently endorsed by a variety of well-known public figures. The purpose of this study is to investigate the impact of celebrities and brand ambassadors on purchase intentions in the e-commerce marketplace. The method employed is an online survey sent to Indonesian fans via direct message on the Instagram official account that posts collaboration ads between the e-commerce marketplace and brand ambassador. To assess the effect of variables, a structural Equation Model (SEM) with AMOS software was used. The study's findings explain the impact of celebrity endorsement and brand love on brand ambassadors purchasing interest, particularly on online shopping sites. Although celebrity endorsement as an exogenous variable is insignificant, all factors of celebrity endorsement show a significant confirmatory factor analysis. Purchase intention is positively influenced by brand passion and affection. This study's marketing implications for related parties are presented.